Determinants of customer’s intention to use Islamic banking products and services: the case of BIMB Dungun branch / Umar Mukhtar Ahmad Foudzi - Ahmad Foudzi, Umar Mukhtar (2013)
This research is about a study on the relationship between the independent variables which is religious obligation, benefit of products and services offered, bank reputations and images, convenience and the dependent variable which is customer’s intention to use Islamic banking..This research will determine the customer’s intention to use Islamic banking and the result of the research indicates that only religious obligation and bank reputations and images positively correlated with the dependent variables. This study is a correlational type of research. There is 196 respondent were made as sample size and this study conduct based on convenience sampling technique. The instrument used in the questionnaire is Likert scale questions and the questionnaire consists of 6 parts. IBM Statistic SPSS 20 was used in order to do the analysis and compute all the data such as reliability analysis, demographic analysis, descriptive analysis, correlational analysis and multiple regression analysis.